2021
DOI: 10.1093/noajnl/vdab101
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review—Time to malignant transformation in low-grade gliomas: Predicting a catastrophic event with clinical, neuroimaging, and molecular markers

Abstract: Background Despite an initially indolent course, all WHO grade II, LGGs inevitably transform to malignant, WHO grades III and IV, without current curative options. Malignant transformation (MT) remains unpredictable with limited prognostic markers to steer timing of interventions. The aim of this study was to review and assign predictive value to specific clinical, molecular and radiological markers impacting MT, thereby justifying timely therapeutic interventions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 75 publications
0
24
0
Order By: Relevance
“…It was found that the mechanism of epilepsy induced by glioma may be that the invasive tumor cells change the excitability of the surrounding normal neurons, making them the pacemakers of seizures. However, the destructive effect of malignant tumors on peripheral neurons and their axons obstructs the occurrence and transmission of epilepsy [ 26 , 27 ]. In addition, patients with tumor over 5 cm accounted for 27.45% in the control group and 52.63% in the observation group, which was larger in the observation group than that in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the mechanism of epilepsy induced by glioma may be that the invasive tumor cells change the excitability of the surrounding normal neurons, making them the pacemakers of seizures. However, the destructive effect of malignant tumors on peripheral neurons and their axons obstructs the occurrence and transmission of epilepsy [ 26 , 27 ]. In addition, patients with tumor over 5 cm accounted for 27.45% in the control group and 52.63% in the observation group, which was larger in the observation group than that in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…GBM tumors are known to either develop de novo or from LGG tumors. In fact, without treatment, LGGs almost always develop into high grade gliomas (Satar et al, 2021). Recent classification of metabolic properties of LGG tumors has been used to identify important genes in the progression of GBM from LGG, including alterations in lipid metabolism (Wu et al, 2019) and glutamate-and calcium-signaling (Pei et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The rate of malignant transformation of LGG ranges from 25% to 72% [ 46 ] and it is influenced by several risk factors, such as preoperative tumor size, velocity of diametric expansion, astrocytoma histology, extent of resection, and treatment with chemotherapy, radiotherapy, and adjuvant chemo-radiotherapy [ 46 ].…”
Section: Discussionmentioning
confidence: 99%